MULA_GuestLecture: A No-code Innovation for Streamlining Online Guest Lecturer Invitation and Digital Approval Processes - หนูทวี, พนิดา; สุขโข, กิตติศักดิ์; อังคุละนาวิน, มฤคินทร์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This action research aimed to: 1) develop the "MULA_GuestLecture" innovation for streamlining the online guest lecturer invitation system using No-code Development technology; 2) compare the operational efficiency between the traditional paper-based system and the developed innovation; and 3) evaluate users' satisfaction levels and technology acceptance based on the Technology Acceptance Model (TAM). The research sample consisted of 30 administrators, course instructors, and support staff at the Faculty of Liberal Arts, Mahidol University, selected through purposive sampling. Research instruments included the MULA_GuestLecture system developed via the Google AppSheet platform, a lead time comparison log, and an online questionnaire. Statistics used for data analysis were percentage, mean, and standard deviation.           The results revealed that the MULA_GuestLecture innovation tangibly enhanced operational efficiency. It effectively reduced the processing time for the digital approval processes from an average of 7 days to only 1-2 working days, thereby mitigating delays and errors associated with the traditional paper-based workflow. Regarding the overall technology acceptance and satisfaction, users were satisfied with the system at the highest level (Mean = 4.60). Users perceived its ease of use and the tangible benefits of real-time data retrieval. The research outcomes have elevated the workflow to a "New Standard Digital Workflow," emphasizing agility, transparency, and a completely paperless environment. This system can serve as a best practice model for transforming routine to research (R2R) for other departments in the future.